Tourette syndrome. The importance of the prevailing attitude and the social problems of the sufferers: literature review - Puzonaitë, B.; Vaitkus, A. (Neurologijos seminarai, 2023)
Background. Tourette syndrome (TS) is not often encountered in the practice of doctors. Biased opinions of the public and doctors prevail about TS, its symptoms are often misunderstood or not recognized in time. This can lead to the development of social problems and stigmatization of the sufferers. Therefore, it is extremely important to rely on scientific research data in order to get a correct understanding of the TS itself and the possible consequences of its misinterpretation for the further social life of children. Aim of the study. To discuss about the clinical characteristics of TS and the importance of correct interpretation; to identify social problems prevalent in children with TS and how these problems can be prevented. Method of the study. The review of scientific literature included publications that were accessible via the Medline database. Inclusion criteria: articles not older than five years, published in English, full text freely available. Exclusion criteria: duplicate articles, publications, information about which did not correspond to the chosen analysed topic. Key words used: Tourette, social problem. Six articles were included in the systematic literature review. Results. Six social problems are identified that have a significant impact on the lives of people with TS: difficulties in communicating and building new relationships, social exclusion, lack of self-worth and self-esteem, poorer academic results, risk of criminality or suicide, and manifestation of the treatment-resistant form of TS. Wider public education, reduction of stigmatization, individual assessment of patient problems and concomitant conditions, and application of targeted treatment methods are extremely important for the management of these problems. Conclusions. Stigmatization and lack of knowledge about TS are common not only among the general public but also among medical professionals. It is important to highlight the need for education about TS for both. Correct interpretation of the disease and early diagnosis can be the first major step to prevent the development of social problems.